A Conceptual Framework for Hispanic Oral Health Care - Gloria C. Mejia, DDS, PhD; Jay S. Kaufman, PhD; Giselle Corbie-Smith, MD; (Blackwell Synergy, 2008)
The need to study the health and health care determinants of US Hispanics is mandated by their rapid population growth.